DIAGNOSTIC YIELD OF COMBINED EPIDEMIOLOGICAL AND RADIOLOGICAL DATA IN MALIGNANT PLEURAL MESOTHELIOMA: A PILOT STUDY - Iqbal, Zafar; Khan, Mohammad Yousaf; Alam, Jamshed; Ullah, Zia (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the diagnostic yield of epidemiological and radiological data in malignant pleural mesothelioma (MPM) patients. Methodology: It was a survey of 56 patients between January 2014 to June 2017 who presented to chest clinic with gradual onset of pulmonary symptoms and had specific abnormal chest radiology. Computerized tomography (CT) guided biopsies were done and samples were sent for analysis for diagnostic yield of MPM. SPSS version 20 was used for statistical analysis. Results: Among the study cases, 30 (53.6%) were male and mean age was 58.79 ±14.383 years). MPM was found in 28 (50%) cases. The diagnostic yield of epidemiological and radiological data showed sensitivity of (82.1%), specificity (14.3%), positive predictive value (48.9%) and negative predictive value (44.4%). The most commonly found marker was Cytokaratin which was present in 71.4% of the mesothelioma patients, followed by Calretinin (57.1%), and WT1 (50%). Conclusion: Mesothelioma was found in half of the study participants. The diagnostic yield of epidemiological and radiological data showed increased sensitivity but low specificity regarding diagnosis of MPM.